Por um modelo morfológico aplicado à análise musical: investigando processos criativos na Sinfonia em Quadrinhos de Hermeto Pascoal - Carvalho, Thiago Cabral (2017)
We present a methodological proposal of musical analysis directed to the study of creativecompositional processes based on the argument that a musical work is an ongoing, changing event, a moving entity that presents itself necessarily in the performance act. The approach involves the study of the entire productive chain that resulted in the musical event when contemplating the technical and socio-contextual dimensions of creation, treating them as indispensable instances for the understanding of their identity. The model consists of three distinct and self-complementary instances to the observation of the musical event within a systemic approach: (1) Analysis of the Artistic Field; (2) Genetic Analysis; (3) CriticalReflexive Analysis. We validate its application through the study of the piece The Comic Strip Symphony (1986) by the Brazilian composer, performer and multi-instrumentalist Hermeto Pascoal (1936). Through methodology, we reach a holistic reading of creation by understanding the process of putting the musical work into practice, placing invariant aspects (COSTA, 2016) based on the understanding of the roles played by the composer and performers in the musical event. We conclude that the method has proved useful both as a speculative tool for musical creation and for performance studies involving this theme.